Nurturing the nation : the family politics of modernizing, colonizing and liberating Egypt, 1805-1923 - Pollard, Lisa (University of California Press, 2005)
Focusing on gender & the family, this text reconsiders the origins of Egyptian nationalism & the revolution of 1919 by linking social changes in class & household structure to the politics of engagement with British colonial rule.